MODERN APPROACHES TO DIAGNOSIS AND MANAGEMENT OF CHRONIC GASTRITIS - Kitayeva Natalya Khamidovna (New modern researchers: modern proposals and solutions, 2025)
Chronic gastritis is a persistent inflammatory condition of the stomach lining that can silently progress over years without producing severe symptoms in the early stages. Historically, the diagnosis and treatment of this disease were based largely on symptom reporting and basic endoscopic findings. However, with the advancement of gastroenterology and molecular diagnostics, modern approaches now enable a more precise, cause-specific understanding and targeted management of chronic gastritis.